2014 44th Annual IEEE/IFIP International Conference on Dependable Systems and Networks 2014
DOI: 10.1109/dsn.2014.103
|View full text |Cite
|
Sign up to set email alerts
|

Optical Delusions: A Study of Malicious QR Codes in the Wild

Abstract: Abstract-QR codes, a form of 2D barcode, allow easy interaction between mobile devices and websites or printed material by removing the burden of manually typing a URL or contact information. QR codes are increasingly popular and are likely to be adopted by malware authors and cyber-criminals as well. In fact, while a link can "look" suspicious, malicious and benign QR codes cannot be distinguished by simply looking at them. However, despite public discussions about increasing use of QR codes for malicious pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 8 publications
0
23
0
Order By: Relevance
“…Kharraz, Kirda, Robertson, Balzarotti and Francillon conducted an empirical analysis across 14 million web pages to discover the extent to which QR codes are leveraged by attackers in the wild. Their results showed that QR codes are being abused by attackers to distribute malware or direct to phishing sites on the public web [3]. The results not only revealed the malicious use of QR codes, but also identified 145 malicious QR codes out of 94,770 QR codes.…”
Section: Leveraging Qr Codes For Phishingmentioning
confidence: 83%
See 2 more Smart Citations
“…Kharraz, Kirda, Robertson, Balzarotti and Francillon conducted an empirical analysis across 14 million web pages to discover the extent to which QR codes are leveraged by attackers in the wild. Their results showed that QR codes are being abused by attackers to distribute malware or direct to phishing sites on the public web [3]. The results not only revealed the malicious use of QR codes, but also identified 145 malicious QR codes out of 94,770 QR codes.…”
Section: Leveraging Qr Codes For Phishingmentioning
confidence: 83%
“…The most prevalent attacks employing QR codes are phishing and drive by downloads [3] that trick users to disclose confidential information. QR codes enable users to open web pages via scanning, without typing the URL.…”
Section: Leveraging Qr Codes For Phishingmentioning
confidence: 99%
See 1 more Smart Citation
“…The attacks described in Section 6.2 exploit the deficiencies of user interfaces in AR browsers, not software vulnerabilities. Other related work includes security threats involving QR codes [15] and the use of QR codes for malware distribution and phishing [17]. Dabrowski et al [5] recently demonstrated numerous attacks involving hiding a QR code inside of another QR code, similar to our our attacks in Section 6.2.…”
Section: Related Workmentioning
confidence: 96%
“…The author was also involved in a set of research papers which are not directly related to this thesis [19,20,55], and would like to thank the collaborators for producing great work in this area.…”
mentioning
confidence: 99%